2008
DOI: 10.1098/rsbl.2008.0481
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic ageing in individual zebra finches

Abstract: Oxidative stress is suggested as a contributor to the ageing process. Knowledge of the relationship between age and energy expenditure may contribute to our understanding of ageing patterns, due to the link between oxygen consumption and free radical production. However, studies on basal metabolic rate (BMR) and age have generally been cross-sectional, which may confound estimates of the age effect due to disproportionate mortality (also known as ‘selective disappearance’). We therefore performed a longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 23 publications
5
64
2
Order By: Relevance
“…The general finding that telomere shortening rate is highest at younger ages suggests that the same occurs between individuals, with individuals with longer telomeres losing base pairs at a higher rate. Note, however, that the observed higher shortening rates in individuals with longer telomeres can also be attributed to other differences between younger and older individuals, such as a decline in metabolic rate (Moe et al 2009). Furthermore, we found no indication for telomere length-dependent shortening rate when comparing between individual nestlings.…”
Section: Discussionmentioning
confidence: 99%
“…The general finding that telomere shortening rate is highest at younger ages suggests that the same occurs between individuals, with individuals with longer telomeres losing base pairs at a higher rate. Note, however, that the observed higher shortening rates in individuals with longer telomeres can also be attributed to other differences between younger and older individuals, such as a decline in metabolic rate (Moe et al 2009). Furthermore, we found no indication for telomere length-dependent shortening rate when comparing between individual nestlings.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate reason for the decline have been suggested to depend on a trade-off between the need for a high work rate, and investment in somatic maintenance and repair mechanisms to counteract the action of e.g. ROS production (Beckman and Ames 1998;Moe et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…One of the physiological indications of senescence is the decline in basal metabolic rate (BMR) with age as found in humans and laboratory animals (e.g. Das et al 2001;Even et al 2001;Roberts and Rosenberg 2006;Moe et al 2009). This results in a decline in mitochondrial energy production (Hunt et al 2006) and a concomitant reduction in energy expenditure (Hulbert and Else 2000;Roberts and Rosenberg 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Speakman et al, 2003;Ruggiero et al, 2008;Moe et al, 2009), whereas others found no BMR change (e.g. O'Connor et al, 2002;Chappell et al, 2003;Moe et al, 2007).…”
Section: Feeding Regimen Feeding Regimenmentioning
confidence: 97%